2010
DOI: 10.1128/aac.00788-09
|View full text |Cite
|
Sign up to set email alerts
|

Ineffectiveness of Tigecycline against Persistent Borrelia burgdorferi

Abstract: The effectiveness of a new first-in-class antibiotic, tigecycline (glycylcycline), was evaluated during the early dissemination (1 week), early immune (3 weeks), or late persistent (4 months) phases of Borrelia burgdorferi infection in C3H mice. Mice were treated with high or low doses of tigecycline, saline (negative-effect controls), or a previously published regimen of ceftriaxone (positive-effect controls). Infection status was assessed at 3 months after treatment by culture, quantitative ospA real-time PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
144
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(155 citation statements)
references
References 78 publications
8
144
3
Order By: Relevance
“…Some have relied on cultivability of the spirochete as the sole measure of antibiotic efficacy, as is conventionally employed for other microorganisms (32,38,39), whereas others have required complete elimination of all spirochetal nucleic acids and proteins (11,14,22,28,40,41). Our study and those of others suggest that the antimicrobial activity of ceftriaxone can be reliably assessed based on cultivability and that cultivation is a more accurate reflection of cell viability.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…Some have relied on cultivability of the spirochete as the sole measure of antibiotic efficacy, as is conventionally employed for other microorganisms (32,38,39), whereas others have required complete elimination of all spirochetal nucleic acids and proteins (11,14,22,28,40,41). Our study and those of others suggest that the antimicrobial activity of ceftriaxone can be reliably assessed based on cultivability and that cultivation is a more accurate reflection of cell viability.…”
Section: Discussionmentioning
confidence: 71%
“…These studies have had various results, and a number of methodological limitations have made the findings difficult to interpret (12,13). Some of these investigations have concluded that viable B. burgdorferi persists in treated animals but in a dormant, noncultivable state (11,14). Analogies have been made with the well-established phenomenon of persistence of small subpopulations in studies of other bacteria when exposed to cidal antibiotics in vitro (15,16).…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…I think that the nosology of post-Lyme disease syndrome has utility and that investigations along the lines of the work described here will yield further insights not just about Lyme disease but about other postinfection sequelae, including reactive arthritis, some forms of chronic fatigue syndrome, and perhaps other disorders yet to be recSchwartz critiqued parts of the experimental designs and the interpretation of the results in these two reports (15). In a subsequent article, Barthold et al rebutted these criticisms and reported additional evidence that "noncultivable" spirochetes in the blood and tissues of treated mice were infectious on the basis of transplantation of tissue allografts and their transmission to naive mice via vector ticks (16). More recently, a paper by Embers et al added more fuel to the fire by concluding on the basis of xenodiagnosis that "B.…”
Section: A Wider Angle Viewmentioning
confidence: 92%